Tradisi Pra-Nikah Kirab Pendopo Perspektif 'Urf - Luluk Devia Karimah (MASADIR: Jurnal Hukum Islam, 2023)
The pendopo carnival tradition is a tradition originating from a sacred village which holds a ritual before the bride and groom say their vows and are encouraged to circle the round stone in front of the pavilion witnessed by local residents who want to see by bringing offerings in the form of food and will share it. when the event is over and the author wants to know whether this tradition has more benefits or mafsadat when carried out. This research is qualitative research or field research using a normative empirical approach. Then the data collection methods used are observation, interviews and documentation. The data sources for this research are community leaders, traditional leaders, religious leaders and related agencies. The results of this research show that the existence of this tradition is believed by the community to be able to minimize unwanted events from occurring (prevent harm) and have an influence on married life, then illustrates the main view of 'urf towards this tradition. The results of this thesis show that the pendopo carnival tradition when viewed from the 'urf perspective is included in the authentic 'urf which does not contain anything that ascribes partners to Allah.